Similar Genetic Architecture of Alzheimer’s Disease and Differential APOE Effect Between Sexes - Wang, Hao; Lo, Min-Tzu; Rosenthal, Sara Brin; Makowski, Carolina; Andreassen, Ole A.; Salem, Rany M.; McEvoy, Linda K.; Fiecas, Mark; Chen, Chi-Hua (Frontiers in Aging Neuroscience, 2021)
Sex differences have been observed in the clinical manifestations of Alzheimer’s disease (AD) and elucidating their genetic basis is an active research topic. Based on autosomal genotype data of 7,216 men and 10,680 women, including 8,136 AD cases and 9,760 controls, we explored sex-related genetic heterogeneity in AD by investigating SNP heritability, genetic correlation, as well as SNP- and gene-based genome-wide analyses. We found similar SNP heritability (men: 19.5%; women: 21.5%) and high genetic correlation (Rg = 0.96) between the sexes. The heritability of APOE ε4-related risks for AD, after accounting for effects of all SNPs excluding chromosome 19, was nominally, but not significantly, higher in women (10.6%) than men (9.7%). In age-stratified analyses, ε3/ε4 was associated with a higher risk of AD among women than men aged 65–75 years, but not in the full sample. Apart from APOE, no new significant locus was identified in sex-stratified gene-based analyses. Our result of the high genetic correlation indicates overall similar genetic architecture of AD in both sexes at the genome-wide averaged level. Our study suggests that clinically observed sex differences may arise from sex-specific variants with small effects or more complicated mechanisms involving epigenetic alterations, sex chromosomes, or gene-environment interactions.